Quantifying the Delays Between Multi-Site Photoplethysmography Pulse and Electrocardiogram R-R Interval Changes Under Slow-Paced Breathing - Allen, John (Frontiers in Physiology, 2019)
Objective: Objective assessment of autonomic function is important, including the investigation of slow paced breathing to induce associated periodic changes in the cardiovascular system - such as blood pressure and heart rate. However, pulse changes across a range of peripheral body sites have seldom been explored with this challenge. The primary aim of this pilot study was to utilize multi-site photoplethysmography (MPPG) technology to quantify the phase delays, i.e. correlation lags, between changes in heart rate and changes in key pulse features with slow paced breathing (0.1 Hz). Methods: Waveforms were collected simultaneously from the right and left ear lobes, thumbs and great toes of 18 healthy adult subjects. Cross correlation lags between reference beat-to-beat changes electrocardiogram R-R wave interval and changes in pulse arrival time (foot of pulse; PATf) and also for pulse amplitude (foot-to-peak; AMP) were determined. Results: Relative to R-R changes the median ear, thumb and toe PATf correlation lags were 3.4, 2.9, and 2.1 beats, respectively; contrasting to AMP with 5.7, 6.0, and 6.9 beats, respectively. These PATf correlation lags in beats were significantly lower than for the AMP measure. Segmental differences between sites and as well as timing measure variability have also been quantified. Conclusion: This pilot study has indicated bilateral similarity plus segmental differences for relative delays in PPG pulse timing and amplitude measures relative to R-R interval changes with paced breathing. These correlation and variability data are now available for comparison with cardiovascular patient groups to support development of autonomic function assessment techniques.